Sosialisasi Sleep Hygiene Mengefektifkan Konsentrasi Belajar Siswa Kelas XI SMA YLPI - Ruzain, Raihanatu Binqalbi; Nurfadila, Syelfi Pasya; Gustari, Jihan Nadia; Fadilla, Nurul (Universitas Pahlawan Tuanku Tambusai, 2025)
Learning concentration can be influenced by several things, one of which is the quality and quantity of sleep. When the quantity of sleep is poor, the dopamine hormone that plays a role in maintaining a state of wakefulness will decrease, so it can cause a decrease in learning concentration in students. To improve students' learning concentration and sleep quality, researchers use the sleep hygiene socialization method for better quality sleep. Currently, some students have poor sleep quality, and it has an impact on their learning process. The purpose of this service activity is to provide knowledge about sleep hygiene to improve the quality and quantity of sleep and streamline student concentration, by providing information related to how to practice good sleep hygiene steps and the benefits of implementing healthy sleep patterns. This activity was carried out on class XI students of SMA YLPI Pekanbaru. The method in this activity is a screening examination in several stages. The results of the service are the increased concentration of students' learning after applying good sleep hygiene practices and their better quality sleep.